ENHANCED THERMAL PERFORMANCE OF POLYETHYLENE GLYCOL-BASED PHASE CHANGE MATERIALS USING ZnO - Fachredzy, Amdy; Manalu, Emmy S.; Sihotang, M. Sontang; Juwono, Ariadne L.; Tetuko, Anggito P.; Fauzi, Muhammad; Nabawi, Muhammad A. H.; Sebayang, Achmad Maulana S.; Setiadi, Eko A. (Universitas Mataram, 2025)
Polyethylene Glycol (PEG), an organic Phase Change Material (PCM) known for its high latent heat capacity and biocompatibility, suffers from poor thermal conductivity. This research explored the addition of ZnO (at 8 and 12 wt.%) as an enhancer and SDBS as a surfactant, utilizing a two-step homogenization process at 80Â°C for 4 h. X-ray Diffraction (XRD) analysis confirmed that no chemical interactions or new phases occurred. Differential Scanning Calorimetry (DSC) findings revealed an enhancement in PEG's latent heat of PEG from 214 J/g to 238.3 J/g (with 8 wt.% ZnO) and 257.7 J/g (with 12 wt.% ZnO). The thermal conductivity improved by 28.2% and 30.3%, respectively, while Thermogravimetric Analysis (TGA) demonstrated increased thermal stability.Â The addition of ZnO can improve the conductivity and thermal stability, while the role of SDBS is significant in increasing the latent heat, making this composite a potential candidate for Thermal Energy Storage system (TES) applications.